Prevalence of Obesity and Overweight among School-Aged Children in Saudi Arabia and Its Association with Vitamin D Status: Prevalence of Obesity in School Children - Al Shaikh, Adnan; Farahat, Fayssal; Abaalkhail, Bahaa; Kaddam, Ibrahim; Aseri, Khalid; Al Saleh, Yousef; Al Qarni, Ali; Al Shuaibi, Ahmed; Tamimi, Waleed (Acta Biomedica Atenei Parmensis, 2020)
Background: Childhood obesity is a significant global public health problem. Worldwide data showed an increasing trend over the years. We aimed to explore the prevalence of obesity, and its association with vitamin D status. Methods: This cross-sectional study was conducted during the period from 2016 to 2017. The study included 3613 schoolchildren aged 6-19 years in the western, central, and eastern regions in Saudi Arabia. Anthropometric data including age, sex and body mass index (BMI) was collected and the serum 25OH- vitamin D (25OHD) was measured. Age-sex standardized BMI Z-scores using the 2007 World Health Organization growth standards were applied. Results: Data from 3613 school-aged children (females = 51.8%), with equal percentage of participants from each region were analyzed. Prevalence of obesity and overweight was estimated at 7.1% and 14.4% respectively. An increasing trend was detected with age (p: 0.006). Obesity started to increase at the age of 10 years and continued to increase until 19 years. Most of the obese children (64.2%) had deficient vitamin D levels, compared to 33.7% of them with suboptimal levels and only 2.0% with optimal levels (p: <0.001). Conclusions: This large cohort study revealed a high prevalence (21.5%) of obesity and overweight in school children aged between 6-19 years with increasing trend with age. Children with high BMI showed extremely high prevalence of VDD and VDI. These findings are alarming and point to the need for effective national interventions that include improving and encouraging access to physical activity and exposure to sunlight, educational activities for students, parents, and schoolteachers and possible enrichment of staple food with vitamin D.